Gene‐Edited Human Kidney Organoids Reveal Mechanisms of Disease in Podocyte Development. (29th September 2017) - Kim, Yong Kyun; Refaeli, Ido; Brooks, Craig R.; Jing, Peifeng; Gulieva, Ramila E.; Hughes, Michael R.; Cruz, Nelly M.; Liu, Yannan; Churchill, Angela J.; Wang, Yuliang; Fu, Hongxia; Pippin, Jeffrey W.; et al.
Abstract: A critical event during kidney organogenesis is the differentiation of podocytes, specialized epithelial cells that filter blood plasma to form urine. Podocytes derived from human pluripotent stem cells (hPSC‐podocytes) have recently been generated in nephron‐like kidney organoids, but the developmental stage of these cells and their capacity to reveal disease mechanisms remains unclear. Here, we show that hPSC‐podocytes phenocopy mammalian podocytes at the capillary loop stage (CLS), recapitulating key features of ultrastructure, gene expression, and mutant phenotype. hPSC‐podocytes in vitro progressively establish junction‐rich basal membranes (nephrin + podocin + ZO‐1 + ) and microvillus‐rich apical membranes (podocalyxin + ), similar to CLS podocytes in vivo. Ultrastructural, biophysical, and transcriptomic analysis of podocalyxin‐knockout hPSCs and derived podocytes, generated using CRISPR/Cas9, reveals defects in the assembly of microvilli and lateral spaces between developing podocytes, resulting in failed junctional migration. These defects are phenocopied in CLS glomeruli of podocalyxin‐deficient mice, which cannot produce urine, thereby demonstrating that podocalyxin has a conserved and essential role in mammalian podocyte maturation. Defining the maturity of hPSC‐podocytes and their capacity to reveal and recapitulate pathophysiological mechanisms establishes a powerful framework for studying human kidney disease and regeneration. Stem Cells 2017;35:2366–2378 Abstract : Comparison of stem cell‐derived human kidney organoids in vitro with genetic mouse models in vivo reveals that podocytes (red), the filtering cells of the kidney, undergo apical‐to‐basal junctional migration at the capillary loop stage. A critical player in this process is podocalyxin, which induces negatively charged microvilli between neighboring podocytes, pushing them apart.